International Architecture News - Grigorieva, Anna (project baikal, 2022)
The news highlights such events as the UIA World Congress and the International Contextual Architecture Awards in memory of Architect Turgut Cansever.
Keywords: International Union of Architects; UN-Habitat; UIA World Congress; international competition